Social-Psychological Factors in the Formation of Personal Identity in Primary School Children - Mustafayeva Dilnoza Qayum qizi (Scientific Trends, 2025)
This article analyzes the process of personal identity formation in primary school-aged children from a socio-psychological perspective. The study examines the role of family, school, teachers, and peers in the development of identity. It also explores the main social factors influencing the formation of a child’s self-image (“I-concept”) and the psychological mechanisms of identification and self-awareness.
Keywords: identity, personal identity, social psychology, primary school age, identification, social factors, self-awareness.